PENGARUH CURRENT RATIO (CR) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2023 - Nurlita, Tri; Sawukir (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of Current Ratio and Total Asset Turnover on Return On Assets. The data used in this research are the financial reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) website for 2018-2023. This research uses quantitative methods and sampling using non-probability sampling techniques. The test tool used is Eviews Version 12. Based on the research results, it can be concluded that the partial Current Ratio test is tcount < ttable = -0.094158 < 2.014103 with a significant value of 0.9255 > 0.05, which means the Current Ratio has no effect and not significant to Return On Assets. Meanwhile, the partial test for Total Asset Turnover is tcount > ttable = 2.198543 > 2.014103 with a significant value of 0.0341 < 0.05, which means that Total Asset Turnover has a significant effect on Return On Assets. Meanwhile, the simultaneous test obtained fcount > ftable= 7.9936283>3.204317 with a significant value of 0.000002 <0.05. It can be said that the Current Ratio and Total Asset Turnover variables simultaneously have a significant effect on Return On Assets.